Seamus Heaney and Theodore Roethke: re-evaluating affinities. Issue 1 (2nd January 2021) - Laverty, Christopher
ABSTRACT: This article examines the echoes of Theodore Roethke in Seamus Heaney's 1960s poetry. Heaney first read Roethke when he was teaching at Queen's University Belfast and was exploring American writing to an extent not acknowledged by his critics, who tend to depict his 1970–71 Berkeley residency as his first confrontation with US poetry. Consideration of Roethke's verse alongside Heaney's Death of a Naturalist (1966) brings into focus several shared features that distinguish Heaney's poetry from that of his British-Irish contemporaries, with whom he was more typically compared in this phase. Though Roethke's "In Praise of Prairie" is now considered by some critics to be the source of Heaney's "Bogland", this level of comparative close reading has not been extended to the two poets' other work. When the childhood pastorals of each poet are read side by side, many other significant points of connection emerge, such as the psychological grammar of the frightened child speaker and the contemplation of a daunting father figure. A strangely overlooked figure in the Heaney pantheon, Roethke was, like Frost, an American poet who was instrumental in the emergence of Heaney's early voice.